2011
DOI: 10.1089/tmj.2010.0089
|View full text |Cite
|
Sign up to set email alerts
|

The Pacific Asynchronous TeleHealth (PATH) System: Review of 1,000 Pediatric Teleconsultations

Abstract: PATH provided patient access to pediatric subspecialty expertise via provider-to-provider asynchronous teleconsultation. Internet-based pediatric subspecialty teleconsultation provides fast, convenient, cost-effective, quality pediatric care to populations of patients who might otherwise require transfer to a distant medical facility for more advanced care. PATH serves as a model for future asynchronous teleconsultation platforms in both the military and civilian healthcare arenas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…Several groups have reported improved access and quality with reduced costs for both adult and pediatric cardiology outpatient evaluations. [92][93][94] Such systems aim to replicate the classic "curbside" consultation for remote providers, thereby extending the reach of the specialist into underserved areas. These programs reduce the need for face-to-face evaluations but can increase the overall number of contacts with the specialist, likely as a result of ready specialist access for primary care providers.…”
Section: Teleconsultation and Tele-auscultation In The Office Teleconmentioning
confidence: 99%
“…Several groups have reported improved access and quality with reduced costs for both adult and pediatric cardiology outpatient evaluations. [92][93][94] Such systems aim to replicate the classic "curbside" consultation for remote providers, thereby extending the reach of the specialist into underserved areas. These programs reduce the need for face-to-face evaluations but can increase the overall number of contacts with the specialist, likely as a result of ready specialist access for primary care providers.…”
Section: Teleconsultation and Tele-auscultation In The Office Teleconmentioning
confidence: 99%
“…Previous research has revealed that the appropriateness of referrals to medical subspecialists/surgical specialists is increased and redundancies in evaluative and diagnostic studies are reduced when telemedicine is used. 9,26,30,31 This situation may be particularly true for children, and especially children with special health care needs. The use of "eReferrals," where primary care providers use a Web-based referral and consultation program to discuss a patient's case with a medical subspecialist/surgical specialist before an in-person referral, is another means by which these technologies can be used to increase efficiencies of care.…”
Section: Efficiencies Of Carementioning
confidence: 99%
“…30,[32][33][34][35][36][37] Savings can be realized by a reduction in the duplication of medical tests and examinations, a reduction in the utilization of higher-cost tertiary care centers, and an increased efficiency in referrals and communication. Beyond these savings, there are many societal benefits, including the reduction in travel and patient transport, a reduction in the hours of missed work by the parent/guardian, and a reduction in the frequency of missed school days.…”
Section: Costs Of Carementioning
confidence: 99%
“…[1][2][3][4][5] Telemedicine, the use of electronic information and communication technologies to provide healthcare over a distance, 6 has been used to address this challenge for over 10 years. [4][5][6][7][8][9] There have been previous reports of high satisfaction and perceived high quality of care in pediatric patients receiving pediatric critical care telemedicine consultations in remote emergency departments (EDs) and adult intensive care units (ICUs). 4,10,11 It has also been shown that telemedicine evaluation has good concordance with in-person evaluation of pediatric patients.…”
Section: Introductionmentioning
confidence: 99%